Free Your Mind: Buddhism, Causality, and the Free Will Problem - Coseru, Christian (Zygon, 2020)
The problem of free will is associated with a specific and significant kind of control over our actions, which is understood primarily in the sense that we have the freedom to do otherwise or the capacity for self-determination. Is Buddhism compatible with such a conception of free will? The aim of this article is to address three critical issues concerning the free will problem: (1) what role should accounts of physical and neurobiological processes play in discussions of free will? (2) Is a conception of mental autonomy grounded in practices of meditative cultivation compatible with the three cardinal Buddhist doctrines of momentariness, dependent arising, and no-self? (3) Are there enough resources in Buddhism, given its antisubstantialist metaphysics, to account for personal agency, self-control, and moral responsibility?